2023
DOI: 10.1186/s12943-023-01716-y
|View full text |Cite|
|
Sign up to set email alerts
|

CMTM6 overexpression confers trastuzumab resistance in HER2-positive breast cancer

Abstract: Human epidermal growth factor receptor 2-positive (HER2+) breast cancer is characterized by invasive growth, rapid metastasis and chemoresistance. Trastuzumab is an effective treatment for HER2+ breast cancer; however, trastuzumab resistance leads to cancer relapse and metastasis. CKLF-like MARVEL transmembrane domain-containing 6 (CMTM6) has been considered as a new immune checkpoint for tumor-induced immunosuppression. The role of CMTM6 in trastuzumab resistance remains unknown. Here, we uncover a role of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Our results suggest that CMTM6 is a novel interacting molecule of CD40. Recent studies have identified CMTM6 as a molecule that interacts with numerous transmembrane proteins, including PD-L1, CD58, and HER2 [16][17][18][19]35 . CMTM6 regulates the membrane levels of these proteins in the post-translational modification pathway, impacting tumor growth and tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that CMTM6 is a novel interacting molecule of CD40. Recent studies have identified CMTM6 as a molecule that interacts with numerous transmembrane proteins, including PD-L1, CD58, and HER2 [16][17][18][19]35 . CMTM6 regulates the membrane levels of these proteins in the post-translational modification pathway, impacting tumor growth and tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic mechanism behind this phenomenon is the stabilization of HER2 protein by CMTM6, which inhibits HER2 ubiquitination. HER2 ubiquitination is a process that promotes HER2 degradation [63,64]. Additionally, CMTM6 is a critical regulator of PD-L1 stability in a broad range of cancer cells, and dual inhibition of HER2 and PD-L1 successfully enhances the anti-tumor effect of anti-HER2 monotherapy in HER2-positive tumor cell [65].…”
Section: The "Input Part" Of the Erbb Network Is A Point To Resolve T...mentioning
confidence: 99%
“…2 HER2 overexpression is associated with a biologically aggressive tumor phenotype, poor prognosis, increased risk of disease recurrence, and limited benefit from chemotherapy. 1,[3][4][5] HER2-directed therapy is standard of care for HER2-expressing unresectable or metastatic breast cancer, HER2-positive locally advanced or metastatic gastric cancers, colorectal and gastroesophageal junction adenocarcinomas, and HER2-mutant non-small-cell lung cancer. [6][7][8][9] However, many patients with other HER2-expressing solid tumors will progress on standard therapy, with poor prognosis and limited alternatives.…”
Section: Introductionmentioning
confidence: 99%